Physical Quality Test Of Rice Bran From Different Milling In Tanah Laut District - Maulana, Fajri; Fajri, Fadhli; Febrina, Bunga Putri; Sandri, Dwi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
This research aims to determine the physical quality of rice bran from different mills in Tanah Laut Regency. Data were collected in this research by means of observation and interviews at five different mills in Tanah Laut, namely Panyipatan, Bumi Makmur, Takisung, Kurau and Pelaihari Districts. Data collection was continued with analysis of the physical quality of the bran in the laboratory. Data was processed manually and analyzed descriptively. The parameters measured for the physical quality of rice bran are water content, pile density, pile compaction density, pile angle and specific gravity. The results of this research show that the physical quality of rice bran from different mills in Tanah Laut Regency has good criteria in terms of water content, namely: 11.18 – 13.31%; stack density 300.00 - 430.00 gram/cm3; pile compaction density 395.04 - 693.45 gram/cm33; stack angle 32.09 - 53.85° and specific gravity 0.219 - 0.143 gram/cm3.